MENGUAK PERMASALAHAN PERPAJAKAN ECOMMERCE DI INDONESIA DAN SOLUSI PEMECAHANNYA - Resha Dwiayu Pangesti Mulyono (Universitas Airlangga, 2017)
This article was written to provide opinions on the taxation of e-commerce in Indonesia from the perspective of government policy by using literature study through information obtained through regulations, documents and supporting data. The purpose of writing this article is to provide feedback on e-commerce taxation that occurred in Indonesia with various types of valuations such as transactions and how e-commerce is done in order to find the gap how to levy taxation of e-commerce activities.Research method used is through the review literature review and the previous research then do the analysis to give an opinion. The result of the research is the revenue authority has an important role in realizing the full potential of ecommerce. According to SE-62 / PJ / 2013 there are four types of e-commerce.In Indonesia in the provisions of the applicable Income Tax Law is article 23/26, provided that the payment is received by a state taxpayer who does not have a P3B with Indonesia. Establishment of a regulatory body is required to monitor the traffic of communication through the internet to prevent the occurrence of crime in cybercrime.Keyword : E-commerce Transactions, Indonesian taxes, OECD Models